2020
DOI: 10.1093/rheumatology/keaa718
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of QRISK3 and SCORE as predictors of carotid plaques in patients with rheumatoid arthritis

Abstract: Objective Because carotid plaques predict the development of cardiovascular events in RA, we aimed to assess if the combined use of the systematic coronary risk evaluation (SCORE) and the QRISK3 algorithms allows for the identification of RA patients with carotid plaques in a defined population-based RA inception cohort. Methods A set of consecutive RA patients without a history of diabetes, chronic kidney disease or cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Our data showed that FRS and QRISK3 can be used in gout patients in future clinical practice. With respect to this, a recent study proposed the combined use of QRISK3 and EULAR-modified SCORE2 as an alternative to the assessment of carotid plaques by ultrasound to identify patients with rheumatoid arthritis at high risk of cardiovascular disease ( 30 ). Therefore, it could be an option to be assessed in patients with gout when an ultrasound study is not available.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that FRS and QRISK3 can be used in gout patients in future clinical practice. With respect to this, a recent study proposed the combined use of QRISK3 and EULAR-modified SCORE2 as an alternative to the assessment of carotid plaques by ultrasound to identify patients with rheumatoid arthritis at high risk of cardiovascular disease ( 30 ). Therefore, it could be an option to be assessed in patients with gout when an ultrasound study is not available.…”
Section: Discussionmentioning
confidence: 99%
“…Combining the QRISK3 and the EULAR modified systematic coronary risk evaluation (mSCORE) algorithms may further optimize the identification of people with rheumatoid arthritis (RA) at high risk for carotid plaques [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The QRISK3 algorithm calculates a person’s risk of developing a heart attack or stroke over the next 10 years. It displays the typical risk of individuals who share the same risk factors as those entered for that individual ( 23 ). In addition, QRISK3 was widely used to estimate CVD risk in SLE and RA ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…It displays the typical risk of individuals who share the same risk factors as those entered for that individual ( 23 ). In addition, QRISK3 was widely used to estimate CVD risk in SLE and RA ( 23 , 24 ). However, only a few studies reported the performances of QRSKI3 in calculating CVD risk related to T2DM ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%